Pamětní zápis: (sepsaný v měsíci srpnu 2005 u příležitosti obšírné opravy kunštátského chrámu sv. Stanislava) - Kundera, Ludvík (Lidé města, 2007)
In 2005, an extensive arrangement of Saint Stanislav’s cathedral was carried out in the Moravian town of Kunštát. At this occasion, the so called balloon, spire cupola, situated under the cross placed on church’s spire was opened. Inside, caskets containing contemporary documents and objects have been discovered. Such type of find happens roughly once every century and the documents and objects are usually selected to inform future generations about town’s (locality’s) conditions at time of the last arrangement or repair of the church. The latest documents and objects from the caskets opened in Kunštát in 2005 date back to 1890, the oldest commemorative document is dated 1687 and is related to the magnanimous transformation of the original gothic church into a baroque building. The final act of the Saint Stanislav cathedral’s roof repair in 2005 was resealing of the balloon into which the old caskets were returned and a new one was added. Its most important part was the so called Commemorative record which is a historicized summary of Kunštát development between 1890 and 2005. Readers of the Urban People revue are lucky since they can read now, at least one hundred years ahead of others when they carefully open the caskets during the next big restoration of the cathedral. The Commemorative record is, apart from its fascinating form of un-mendacious résumé, also interesting because of the extraordinary name of the author, namely Ludwik Kundera, the “prince of Moravian poetry”, honorary citizen of Kunštát and important playwright and legendary translator. It might be worth it to find out how many balloons of Czech, Moravian, and Silesian churches during the past two centuries contain a “message for future generations” that was written by contemporary and during their lifetime renowned poet, novelist, historian, teacher or priest whose significance exceeded beyond parish borders of a given church.